ANALISIS PENGARUH PANDEMI COVID-19 SEBAGAI KATALIS DALAM PERKEMBANGAN TELEMEDICINE DI INDONESIA: SEBUAH NARRATIVE REVIEW - Ardyles Ardyles; Yaslis Ilyas (Jurnal Kesehatan Masyarakat (Undip), 2022)
Telemedicine is one of the health services that is widely used in the world along with the development of information and communication technology.  Indonesia has formulated Telemedicine service regulation in “Peraturan Menteri Kesehatan Number 90 Year 2015”. However, the existing guidelines are not comprehensive to cover Telemedicine in Indonesia, especially during Covid-19 pandemic. This study aim is to analyze the effect of Covid-19 pandemic in accelerating the development of Telemedicine in Indonesia. This review process is carried out through a systematic review from supporting sources. The result shows that during Covid-19 pandemic, Indonesia Government facilitated Telemedicine service program for non-emergency health cases, meanwhile researches related to the implementation of Telemedicine in hospitals are started. The data obtained demonstrates the Covid-19 pandemic has a role as catalyst in the development of Telemedicine in Indonesia.